Synthesis, Characterization, and Biotoxicity of NN⌢ Donor Sulphonamide Imine Silicon(IV) Complexes - Mukta Jain; R. V. Singh (Bioinorganic Chemistry and Applications)
The organosilicon derivatives of 2-[1-(2-furayl)ethyledene]sulphathiazole with organosilicon chlorides have been synthesised and characterized on the basis of analytical, conductance, and spectroscopic techniques. Probable trigonal bipyramidal and octahedral structures for the resulting derivatives have been proposed on the basis of electronic, IR, 1H, 13C NMR, and 29Si NMR spectral studies. In the search for better fungicides, bactericides, nematicides, and insecticides studies were conducted to assess the growth-inhibiting potential of the synthesized complexes against various pathogenic fungal, bacterial strains, root-knot nematode Meloidogyne incognita, and insect Trogoderma granarium These studies demonstrate that the concentrations reached levels which are sufficient to inhibit and kill the pathogens, nematode, and insect.